Effect of air agent on mechanical properties and microstructure of lightweight geopolymer concrete under high temperature. (June 2022) - Tayeh, Bassam A.; Hakamy, Ahmad; Amin, Mohamed; Zeyad, Abdullah M.; Agwa, Ibrahim Saad
Abstract: Recent innovations in the field of concrete have contributed to the development of lightweight geopolymer concrete (LGC), which can be produced by adding an air agent. This study investigates the possibility of producing an air agent from the powder slag of ferrosilicon (FSS), an industrial waste. A class F fly ash (FA) was used for GC synthesis, and aluminium powder (AP) and FSS were added as air agents for LGC synthesis. The performance of FSS and AP as an air agents was compared by studying the properties of LGC produced under the same conditions. Air agents with 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% and 1.0% mass of FA were adopted to produce LGC. Thirteen mixtures were prepared to evaluate unit weight, the fresh and mechanical properties and the microstructure of LGC with PA and FSS air agents. Influence of high temperature of 200–800 °C for 2hrs on LGC was also investigated. The results show the possibility of using FSS waste powder as an air agent in LGC production. In terms of workability and unit weight, FSS was better compared to AP at the same percentage addition. The slump flow and unit weight, were 548 mm, 1830 kg/m 3, and 569 mm and 1740 kg/m 3, while compressive strength was 24.7 and 21.8 MPa for LGC containing 1% AP and 1% FSS, respectively.